2020
DOI: 10.3390/cancers12040949
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alternative Lengthening of Telomeres Mechanism in Cancer: Translational and Therapeutic Implications

Abstract: Telomere maintenance mechanisms (i.e., telomerase activity (TA) and the alternative lengthening of telomere (ALT) mechanism) contribute to tumorigenesis by providing unlimited proliferative capacity to cancer cells. Although the role of either telomere maintenance mechanisms seems to be equivalent in providing a limitless proliferative ability to tumor cells, the contribution of TA and ALT to the clinical outcome of patients may differ prominently. In addition, several strategies have been developed to interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 59 publications
(144 reference statements)
1
42
0
1
Order By: Relevance
“…Recently, comprehensive whole-genome analysis has identified that the accumulation of point mutations within the promoter region of the hTERT gene is responsible for the increased TERT expression [13]. Only in a minority of cancer, telomere length maintenance is achieved by telomerase-independent mechanisms, referred to as "alternative lengthening of telomeres" (ALT) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, comprehensive whole-genome analysis has identified that the accumulation of point mutations within the promoter region of the hTERT gene is responsible for the increased TERT expression [13]. Only in a minority of cancer, telomere length maintenance is achieved by telomerase-independent mechanisms, referred to as "alternative lengthening of telomeres" (ALT) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Telomeric DNA ranges from 3 to 15 Kb in humans, leaving a G-rich 3'-single-strand extended beyond the complementary chain, usually called the G-overhang [1,2]. To avoid the end-protection problem due to the overhang chain, the G-tail folds into itself, invading the double-stranded telomeric DNA, forming a lasso-like structure called the t-loop [3], which is protected by a six protein complex called shelterin [4], essential for telomere replication and regulation [2,3]. The shelterin complex is composed of the telomeric repeat binding factors 1 and 2 (TRF1 and TRF2), which interact with the telomeric double-stranded DNA and the protection of telomeres 1 (POT1) that bind to the single-stranded DNA [5].…”
Section: Introductionmentioning
confidence: 99%
“…A high proportion of tumors reactivate the expression of telomerase to maintain its chromosomal ends, while 10-15% of human cancers use the ALT pathway [7]. ALT is frequently detected in tumors of mesenchymal or neuroephitelial origin [8], but there have been reports of the ALT mechanism detected in a fraction of epithelial tumors like: breast, skin, ovarian, uterus and gastric, among others [3,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations